Developmental Controls are Re-Expressed during Induction of Neurogenesis in the Neocortex of Young Adult Mice - Sohur, U. Shivraj; Arlotta, Paola; Macklis, Jeffrey D. (Frontiers in Neuroscience, 2012)
Whether induction of low-level neurogenesis in normally non-neurogenic regions of the adult brain mimics aspects of developmental neurogenesis is currently unknown. Previously, we and others identified that biophysically-induced, neuron subtype-specific apoptosis in mouse neocortex results in induction of neurogenesis of limited numbers of subtype-appropriate projection neurons with axonal projections to either thalamus or spinal cord, depending on the neuron subtype activated to undergo targeted apoptosis. Here, we test the hypothesis that developmental genes from embryonic corticogenesis are reactivated, and that some of these genes might underlie induction of low-level adult neocortical neurogenesis. We directly investigated this hypothesis via microarray analysis of microdissected regions of adult mouse neocortex undergoing biophysically activated targeted apoptosis of neocortical callosal projection neurons (CPN). We compared the microarray results identifying differentially expressed genes with public databases of embryonic developmental genes. We find that, following activation of subtype-specific neuronal apoptosis, three distinct sets of normal developmental genes are selectively re-expressed in neocortical regions of induced adult neurogenesis: 1) genes expressed by subsets of progenitors and immature neurons in the developing ventricular and/or subventricular zones; 2) genes normally expressed by developmental radial glial progenitors; and 3) genes involved in synaptogenesis. Together with previous results, the data indicate that at least some developmental molecular controls over embryonic neurogenesis can be re-activated in the setting of induction of neurogenesis in the adult neocortex, and suggest that some of these activate and initiate adult neuronal differentiation from endogenous progenitor populations. Understanding molecular mechanisms contributing to induced adult neurogenesis might enable directed CNS repair.